2018
DOI: 10.3847/1538-4357/aaa54b
|View full text |Cite
|
Sign up to set email alerts
|

The Origin of Molecular Clouds in Central Galaxies

Abstract: We present an analysis of 55 central galaxies in clusters and groups with molecular gas masses and star formation rates lying between 10 8 − 10 11 M and 0.5 and 270 M yr −1 , respectively. Using Chandra X-ray observations, we have calculated hydrostatic mass profiles, fully accounting for the central galaxy. We have derived acceleration profiles, atmospheric temperature, density, and other thermodynamic variables. Molecular gas mass is correlated with star formation rate, Hα line luminosity, and central atmosp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
158
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(176 citation statements)
references
References 112 publications
(185 reference statements)
18
158
0
Order By: Relevance
“…We speculate that colder, likely molecular gas is present in the central regions of A2495. This is supported by the correlation between the Hα luminosity and the molecular mass (Edge 2001; Pulido et al 2018), from which we obtain M mol ∼ 10 9 M . The contrast with the estimate determined from the dust/gas ratio is only apparent: the latter takes into account the dust mass within the central 7 kpc of the BCG and constitutes, per se, a lower limit (see above).…”
Section: Optical Analysissupporting
confidence: 73%
See 1 more Smart Citation
“…We speculate that colder, likely molecular gas is present in the central regions of A2495. This is supported by the correlation between the Hα luminosity and the molecular mass (Edge 2001; Pulido et al 2018), from which we obtain M mol ∼ 10 9 M . The contrast with the estimate determined from the dust/gas ratio is only apparent: the latter takes into account the dust mass within the central 7 kpc of the BCG and constitutes, per se, a lower limit (see above).…”
Section: Optical Analysissupporting
confidence: 73%
“…The warm and cold gas show correlations with each other and with the hot ICM (Crawford et al 1999;Edge 2001;Hogan et al 2017;Pulido et al 2018), which strongly suggest that hot gas cooling (albeit reduced with respect to the classical cooling flow model) is the origin of the observed cold gas. Observations, simulations and analytic investigations agree that spatially extended cooling is likely to occur in dense cool cores with short cooling times (or cooling time/dynamical time ratio below certain threshold, e.g., Hogan et al 2017;Pulido et al 2018, and references therein). The multiphase medium in cluster cores also reveals a complex dynamics, likely the result of AGN activity and merging events.…”
Section: Introductionmentioning
confidence: 82%
“…Condensation into multi-phase can take place when locally t cool /t ff < 1, but it is also observed for larger values of the radial t cool /t ff profile due to the turbulence and inhomogeneities injected by uplifting hot gas from the cluster center via AGN driven feedback processes (Voit et al 2017;Voit 2018). It has been confirmed observationally that molecular gas is observed at the minima of t cool /t ff profiles (Hogan et al 2017;Pulido et al 2018;Olivares et al 2019), with some of these authors stressing that only t cool determines condensation rates as the growth of linear perturbations is largely independent of the geometry of the gravitational potential (Choudhury & Sharma 2016). Simulations have shown that the turbulence injected by AGN feedback can cause the local thermal instabilities predicted by McCourt et al (2012), but struggle to reproduce the observed morphologies, with dense gas having either a very clumpy morphology (Li & Bryan 2014b;Yang & Reynolds 2016a) or settling into a massive central disk (Gaspari et al 2012;Li & Bryan 2014a,b;Prasad et al 2015).…”
Section: Introductionmentioning
confidence: 89%
“…Molecular mass fraction from IRAM observations (blue leftward pointing triangles) and those based extrapolating the CO measurements assuming a constant Hα-to-CO flux ratio (red stars; see text for details) over total molecular masses from ALMA. The IRAM measurements are taken from Edge (2001); Salomé & Combes (2003); Pulido et al (2018). The measured and expected mass of the molecular gas in RXJ0821+0752 is almost the same.…”
Section: Evidence Supporting That Cold and Ionized Emissionmentioning
confidence: 99%